2019
DOI: 10.1101/626390
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Triphenyl phosphate is a selective PPARγ modulator that does not induce brite adipogenesis in vitro and in vivo

Abstract: Background: Triphenyl phosphate (TPhP) is an environmental PPARγ ligand, and growing evidence suggests that it is a metabolic disruptor. We have shown previously that the structurally similar ligand, tributyltin, does not induce brite adipocyte gene expression.Objectives: First, we tested whether TPhP also fails to induce brite adipogenesis in vivo, in human primary preadipocytes and in 3T3 L1 cells. Second, we tested the hypothesis that TPhP is a selective PPARγ modulator that is unable to protect PPARγ from … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Since the biological effect of PPAR activation is directly related to the metabolism of lipids and carbohydrates, the main axis of biomarkers studied are the genes containing in their promoter the PPRE and the enzymes/proteins encoded by these genes in the main organs controlling the energetic homeostasis of the organism; the biomarkers used to monitoring PPAR activation through pesticides could be summarized as follows: the biological activation of the PPAR has been observed in adipose tissue by DDT, dieldrin, diazonin, fenthion, and fibronil through the accumulation of lipids as an effect of adipocyte maturation [22,33,38,50]. Also this activation has been observed with organophosphate flame retardants (OPFRs) in inducing adipogenesis as 2-ethylhexyl diphenyl phosphate (EHDPP) [114] and triphenyl phosphate (TPHP) [115]; however, by exploring the mechanism by which pesticides enable this accumulation, it has been shown that the role of PPARγ in this phenomenon is important and consistent, but not unique, as accumulation of lipids is still observed despite blocking the receptor, as in the case of qhizalofop-ethyl [39]; and even the direct role of other receptors in lipid accumulation has been reported, as in the case of dioxin: 2,3,7,8-tetrachlorodibenzo-p-dioxin, which is antagonistic to the aryl hydrocarbon receptor (AhR) and prevents lipid accumulation in association with a decrease in PPARγ [116]. Likewise, the mechanism of lipid accumulation has been shown to be 23 PPAR Research not only due to a process of direct activation of nuclear receptors, as is the case with chlorantraniliprole and pyraclostrobin, which increase oxidative stress in the ER and mitochondria, accordingly, caused by an increase in lipid peroxidation and ROS, and decrease the availability of ATP [23,40].…”
Section: Discussionmentioning
confidence: 99%
“…Since the biological effect of PPAR activation is directly related to the metabolism of lipids and carbohydrates, the main axis of biomarkers studied are the genes containing in their promoter the PPRE and the enzymes/proteins encoded by these genes in the main organs controlling the energetic homeostasis of the organism; the biomarkers used to monitoring PPAR activation through pesticides could be summarized as follows: the biological activation of the PPAR has been observed in adipose tissue by DDT, dieldrin, diazonin, fenthion, and fibronil through the accumulation of lipids as an effect of adipocyte maturation [22,33,38,50]. Also this activation has been observed with organophosphate flame retardants (OPFRs) in inducing adipogenesis as 2-ethylhexyl diphenyl phosphate (EHDPP) [114] and triphenyl phosphate (TPHP) [115]; however, by exploring the mechanism by which pesticides enable this accumulation, it has been shown that the role of PPARγ in this phenomenon is important and consistent, but not unique, as accumulation of lipids is still observed despite blocking the receptor, as in the case of qhizalofop-ethyl [39]; and even the direct role of other receptors in lipid accumulation has been reported, as in the case of dioxin: 2,3,7,8-tetrachlorodibenzo-p-dioxin, which is antagonistic to the aryl hydrocarbon receptor (AhR) and prevents lipid accumulation in association with a decrease in PPARγ [116]. Likewise, the mechanism of lipid accumulation has been shown to be 23 PPAR Research not only due to a process of direct activation of nuclear receptors, as is the case with chlorantraniliprole and pyraclostrobin, which increase oxidative stress in the ER and mitochondria, accordingly, caused by an increase in lipid peroxidation and ROS, and decrease the availability of ATP [23,40].…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricle samples from 4 mice/group were processed as previously described (22,(40)(41)(42). Briefly, freshly thawed samples were homogenized on ice in with a mixer mill MM 400 (Retsch USA Verder Scientific Inc., Newtown, PA, United States) in 10 volumes of 8 M urea, 50 mM ammonium bicarbonate, 2 mM dithiothreitol, and protease and phosphatase inhibitor cocktails (Roche Applied Science, Indianapolis, IN, United States).…”
Section: Tissue Sample Preparation For Proteomics and Phosphoproteomicsmentioning
confidence: 99%
“…Differences in conformation not only determine the efficacy to which PPARγ is activated but also the transcriptional repertoire (Chrisman et al 2018). We have shown recently, for instance, that TPhP did not protect PPARγ from phosphorylation at s273 and did not induce brite adipogenesis; however, when PPARγ cannot be phosphorylated at s273, TPhP could induce brite adipogens (Kim et al 2020). Structural analyses would need to be conducted with each environmental ligand specifically to determine the contribution of conformational changes to the biological activity.…”
Section: Adipogen Taxonomy Identifies Environmental Chemicals That Favor White Adipogenesismentioning
confidence: 99%
“…As a result, TBT-induced adipocytes failed to up-regulate mitochondrial biogenesis and had low levels of cellular respiration (Kim et al 2018;Shoucri et al 2018). The structurally similar environmental PPARγ ligand, triphenyl phosphate, also fails to induce brite adipogenesis, and this correlates with an inability to prevent PPARγ from being phosphorylated at Serine 273 (S273) (Kim et al 2020).…”
Section: Introductionmentioning
confidence: 99%